Study on Modelling and Simulation of Wastewater Biochemical Treatment Activated Sludge Process - Du, X.J.; Hao, X.H.; Li, H.J.; Ma, Y.W. (Asian Journal of Chemistry, 2011)
International Water Association and the European Co-operation in the field of Scientific and Technical Research (COST) action 682/624 develop the activated sludge wastewater treatment Benchmark simulation model No. 1 (BSM1). The main purpose is to establish an activated sludge process control program development platform. This paper describes how to use Matlab M-files to establish BSM1 and then gives out the results of the model simulation.